2006
DOI: 10.1063/1.2374844
|View full text |Cite
|
Sign up to set email alerts
|

Electronic density tailing outside π-conjugated polymer surface

Abstract: A systematic density functional theory study of the electronic structure of bulk and (001) surface of transitionmetals carbides Penning ionization electron spectroscopy ͑PIES͒ was adopted to examine surface electronic property of conjugated poly͑3-hexylthiophene͒ ͑P3HT͒ aiming to detect the electronic density tailing outside a polymer surface. The electronic wave function of the highest occupied molecular orbital ͑HOMO͒ state is shielded by side hexyl chain for a P3HT film with edge-on conformation and was not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 22 publications
0
29
1
Order By: Relevance
“…51 Near-edge x-ray absorption fine structure spectroscopy (NEXAFS) (Refs. [22][23][24] can also be used to determine the orientation of thiophene ring and hexyl groups at the interface. It is therefore possible to directly compare our simulation results with experiment.…”
Section: B Molecular Orientationmentioning
confidence: 99%
See 2 more Smart Citations
“…51 Near-edge x-ray absorption fine structure spectroscopy (NEXAFS) (Refs. [22][23][24] can also be used to determine the orientation of thiophene ring and hexyl groups at the interface. It is therefore possible to directly compare our simulation results with experiment.…”
Section: B Molecular Orientationmentioning
confidence: 99%
“…Using NEXAFS for regioregular P3HT thin films at air/film interfaces, several average tilt-angle measurements of thiophene ring have been reported. [22][23][24] Ho et al 24 found tilt angles for spin-casted thin film, using different solvents, of 57 • -60 • and drop-cast thin-film P3HT of 59 • . Hao et al 22,23 investigated the orientation of the thiophene ring for different thin-film samples.…”
Section: Thiophene Ring Orientationmentioning
confidence: 99%
See 1 more Smart Citation
“…On polymer samples, MAES has been used as a powerful method to determine the molecular orientation at the surface because the obtained spectra directly reflect the electron density distributed at the outermost surface of the specimens. [28][29][30] In the present study, we carried out X-ray photoelectron spectroscopy (XPS), ultraviolet photoelectron spectroscopy (UPS), and MAES integrally on the MoO 3 -on-F8BT interfaces for the sake of clarifying the mechanism for the improvement of hole-injection characteristics from the top anodes being realized by the MoO 3 interlayers. Figure 1 shows the UPS and MAES spectra of the F8BT film plotted together with the ab initio molecular orbital (MO) calculation results (GAMESS [31] with B3LYP/6-31G Ã basis set) for the monomer of F8BT as a reference.…”
mentioning
confidence: 99%
“…Taking into consideration that MAES is an extremely surface sensitive method, the absence of MAES intensity at the top-valence region suggests that the backbones of F8BT are not exposed to the outermost surface of the film, probably because they lie beneath the octyl side-groups. [29,30] It is interesting to note that the spectral shape of the MAES resembled that of normal alkanes standing upright in their crystalline phase. [34] This fact also supports the idea that the MAES signals predominantly came from the methyl terminals of the octyl side chains.…”
mentioning
confidence: 99%